Solve the equation in real number.

\[\sqrt{2+\sqrt{2+\sqrt{2+x}}} + \sqrt{3}\sqrt{2-\sqrt{2+\sqrt{2+x}}} = 2x\]

I've got an idea that \(0 \leq x \leq 2\), but I can't continue further.

Help me!

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestSubstitute \(x=2\cos(\theta)\)

\(\therefore\) \(\sqrt{2+\sqrt{2+\sqrt{2+2\cos(\theta)}}} + \sqrt{3}\sqrt{2-\sqrt{2+\sqrt{2+2\cos(\theta)}}}= 4\cos(\theta)\)

Now, \(2+2\cos(\theta)= 2(1+\cos(\theta))= 4cos^{2}(\theta/2)\)

Hence are equation becomes: \(\sqrt{2+\sqrt{2+2|\cos(\theta/2)|}}+ \sqrt{3}\sqrt{2-\sqrt{2+2|\cos(\theta/2)|}}=4\cos(\theta)\)

Repeat this process till you eliminate the radicals( it will take you two more steps).

Note: In the last step you will have to use \(1-\cos(\theta/4)=2\sin^{2}(\theta/8)\)

So finally we arrive at : \( 2|\cos(\theta/8)|+2\sqrt{3}|\sin(\theta/8)|=4\cos(\theta)\)

\(\therefore\) \(\dfrac{1}{2}|\cos(\theta/8)|+ \dfrac{\sqrt{3}}{2}|\sin(\theta/8)|=\cos(\theta)\)

\(\text{CASE 1: When \theta lies in the first quadrant}\)

\(\bullet\) \(\cos(\theta/8-\pi/3)=cos(\theta)\)

\(\text{CASE 2: When theta lies in the second quadrant}\)

\(\bullet\) \(-\cos(\theta/8+\pi/3)= cos(\theta)\)

\(\text{CASE 3: When theta lies in the third quadrant}\)

\(\bullet\) \(-\cos(\theta/8-\pi/3)=cos(\theta)\)

\(\text{CASE 4: When theta lies in the fourth quadrant}\)

\(\bullet\) \(\cos(\theta/8+\pi/3)= cos(\theta)\)

Solve this general equation for \(\theta\), take the union of all cases and plug the permissible values in \(x=2\cos(\theta)\), to find your desired solutions.

Feel free to ask if you have a doubt at any point.

Log in to reply

Great work!!

However, you will need to be careful, that \( \sqrt{ \cos^2 \theta } = | \cos \theta | \). So, after the last step, proceed with caution.

Note that in the second line, the RHS should be \( 4 \cos ^2 ( \theta / 2 ) \).

Log in to reply

Oh yes, I had completely forgotten that, Thanks a ton sir, for your inputs!

Log in to reply

Sir, but \(0\leq x \leq 2\), Hence \(0\leq y \leq 1\), where \(y=\cos(\theta)\) So the modulus here has no importance, right?

Log in to reply

Putting this together, we actually have \( -2 \leq x \leq 2 \). So, you should verify the assumptions, especially when it's phrased as "I have an idea that this might work". It just might be possible that we have negative solutions.

Secondly, (for sake of argument) suppose you found that \( \theta = \frac{ 7 \pi } { 4} \) was a solution. Is this truly a solution? The issue arises because even though \( \cos \theta > 0 \), we actually end up with \( \cos \frac{ \theta } { 2} < 0 \). As such, we actually have \( \sqrt{ 2 + 2 \cos \theta } = - \cos \frac{ \theta} {2} \neq \cos \frac{ \theta}{2} \) IE we need to take the negative square root.

Log in to reply

Log in to reply

Log in to reply

Log in to reply

Try some trigonometry.

Log in to reply

I haven't been able to work on this, Sir, But the range \(0\le x\le2\) made me think of the substitution \(x=X+1\). Therefore, \(X\in[-1,1]\) which immediately reminds one of \(\sin\theta\) or \(\cos\theta\).

Log in to reply

I think it would be better if you would cosider x=2X rather than x=X+1 and then you can use trigo.

Log in to reply

Log in to reply

Hint:Conjugates.Log in to reply